Design and Analysis of Aero-engine Central Transmission based on Face Gear Transmission - Wenshuang Teng; Mei Guo; Ning Zhao; Hui Guo (Jixie chuandong)
To systematically evaluate the problems of insufficient load capacity，mass over limit， low stability caused by the application of traditional gear transmission in aero-engine high-power extraction transmission system， the central transmission of aero-engine based on face gear transmission is designed， the LTCA is performed， and the contact area ratio and stress are calculated. It is concluded that the central transmission based on face gear transmission has the advantages of high load capacity， light weight and good running stability， face gear transmission can provide a new transmission design route for the existing aero-engine transmission system.